2009
DOI: 10.1128/jb.00425-09
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intracellular Polysaccharide in Persistence of Streptococcus mutans

Abstract: Intracellular polysaccharide (IPS) is accumulated byStreptococcus mutans when the bacteria are grown in excess sugar and can contribute toward the cariogenicity of S. mutans. Here we show that inactivation of the glgA gene (SMU1536), encoding a putative glycogen synthase, prevented accumulation of IPS. IPS is important for the persistence of S. mutans grown in batch culture with excess glucose and then starved of glucose. The IPS was largely used up within 1 day of glucose starvation, and yet survival of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 37 publications
0
62
0
5
Order By: Relevance
“…Lack of EPS disrupts both adherence of bacteria and the structure of biofilm. When exogenous substrate is depleted, S. mutans can metabolize IPS [50]. Therefore, malfunction of GTFs not only directly disrupt the biofilm integrity, but also may enhance the starvation stress of S. mutans due to reduced preservation of IPS.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of EPS disrupts both adherence of bacteria and the structure of biofilm. When exogenous substrate is depleted, S. mutans can metabolize IPS [50]. Therefore, malfunction of GTFs not only directly disrupt the biofilm integrity, but also may enhance the starvation stress of S. mutans due to reduced preservation of IPS.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of IPS has been implicated in enhanced survival of S. mutans and has been shown to contribute to caries formation (Gibbons & Socransky, 1962;Spatafora et al, 1995;van Houte et al, 1970). Previous work revealed that production of IPS via glgA (encoding glycogen synthase) significantly extended the survival of S. mutans during starvation, especially when cells were grown in the presence of glucose (Busuioc et al, 2009). The upregulation of several glg genes led us to hypothesize that the enhanced long-term survival of DclpP and DclpX (Kajfasz et al, 2009) could be associated with increased IPS storage.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of stored IPS was evaluated by using a colorimetric assay that relies on the formation of an iodinepolysaccharide complex (Busuioc et al, 2009). Briefly, bacteria were streaked on Todd-Hewitt agar plates containing 2 % glucose or 2 % sucrose and incubated for 48 h. The plates were then flooded with 5 ml iodine solution [0.2 % (w/v) iodine in 2.0 % (w/v) potassium iodide solution].…”
Section: Methodsmentioning
confidence: 99%
“…The malfunction of GTFs at the lower pH value may lead to reduced production of EPS and IPS. The latter can be metabolized when exogenous fermentable substrate is depleted in the oral cavity (10). Therefore, the malfunction of GTFs may disrupt both bacterial adherence to the tooth surface and biofilm integrity and may augment the starvation stress of S. mutans cells due to the reduced preservation of IPS.…”
Section: Discussionmentioning
confidence: 99%